Simulation and analysis of battery performance of a solar car using a model implemented in simulink - Al Maliniud, Abdullah; Zaman, Asif; Jafar, Imran Bin (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2nd International Conference on Electrical Information and Communication Technologies, EICT 2015; Khulna; Bangladesh; 10 December 2015 through 12 December 2015 [ © 2015 IEEE ] The conference paper's definite version is available at: http://dx.doi.org/10.1109/EICT.2015.7391999